PEMAHAMAN AJARAN LAWAN SASTRA NGESTI MULYA DAN HEDONIC MOTIVATION TERHADAP PENGGUNAAN SHOPEE PAYLATER â€œBELI SEKARANG BAYAR NANTIâ€ - Wardani, Dewi Kusuma; Indra, Indra (JURNAL EKOBIS DEWANTARA, 2024)
This study aims to determine the influence of understanding the teaching of lawan sastra ngesti mulya and hedonic motivation on the use of shopee paylater â€œbuy now pay laterâ€. The population of this study consisted of students studying in the Special Region Of Yogyakarta. A total of 104 respondents were given questionnaires as part of the quantitative method of this study, which also used snowball sampling techniques to obtain data. According to the research findings, the hedonic motivation variable has a positive effect on the use of shopee paylater, although understanding the teachings of lawan sastra ngesti mulya has no effect on the use of shopee paylater â€œbuy now pay laterâ€.